2016
DOI: 10.1108/heswbl-02-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate employability training and employment: a UAE study

Abstract: Purpose – The purpose of this paper is to investigate the link between female undergraduate student participation in a university-sponsored employment skills development program and employment post-graduation. Design/methodology/approach – From historical institutional data a random sample was analyzed using the logistic regression model. The main variable investigated was participation in the World of Work (WOW) program during undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
3
11
1
1
Order By: Relevance
“…These findings are consistent with those of previous studies on graduate employability (Caldwell and O’Reilly, 1990; Capobianco, 2009; Kristof-Brown, 2000; Mulligan, 2017; O’Reilly et al, 1991; Schmitt and Chan, 1998). However, the results differ somewhat from the findings of Temtamy et al (2016), who highlight academic scores, campus location and major subject as the primary contributors to graduate employability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies on graduate employability (Caldwell and O’Reilly, 1990; Capobianco, 2009; Kristof-Brown, 2000; Mulligan, 2017; O’Reilly et al, 1991; Schmitt and Chan, 1998). However, the results differ somewhat from the findings of Temtamy et al (2016), who highlight academic scores, campus location and major subject as the primary contributors to graduate employability.…”
Section: Discussioncontrasting
confidence: 99%
“…Dhingra ( 2018) also found that the letter of application and external recommendations were of negligible importance, while specialization, academic scores and the reputation of the institution moderately affected selection decisions during campus recruitment. El-Temtamy et al (2016) found that marks, campus location and the subject of study positively supported graduate employability and increased the chances of employment on graduation. Capobianco (2009) highlights that less importance is given to the academic institution's reputation by employers than is usually assumed by prospective students when they are choosing an HEI.…”
Section: Factors Affecting Employers' Selection Decisionmentioning
confidence: 97%
“…Even acknowledging the limitations of these reports as the sole source of data to claim that actual learning has occurred, or that an ideal learning has been achieved, the statements of the students substantiate that the PAP experience is meaningful to them and achieves the central WBL aim of the program: to allow the students to apply prior knowledge and learn through practice in an "authentic" environment. Particular aspects of reported learning echo findings of other researchers, for example that students develop self-confidence through placement experiences (Edwards, 2014), that students in placements develop specific competencies that foster employability (Wilton, 2014;Helyer and Lee, 2014), and that they also develop "generic skills," and soft competencies such as teamwork, communication and attitude to work (El-Temtamy et al, 2016;Miller et al, 2013). Other aspects present in students' reports that are less discussed in the work-based learning literature are being a change agent and doing social service through placements.…”
Section: Discussionsupporting
confidence: 62%
“…By implementing English training programs through this approach, knowledge and skills can be shared between employers and employees. Successful transfer of skills leads to the development of the competency of workers (El-Temtamy et al, 2016). Nagarajan and Edwards (2015), claim that the transfer of knowledge and skills prepares employees to be competitive in the challenging job market.…”
Section: Trainingmentioning
confidence: 99%